2020
DOI: 10.1371/journal.pone.0243538
|View full text |Cite
|
Sign up to set email alerts
|

Maternal lipid profile and risk of pre-eclampsia in African pregnant women: A systematic review and meta-analysis

Abstract: Introduction Some studies have reported the association between maternal serum lipid profile abnormalities and pre-eclampsia. However, many studies have reported controversial results. Hence, this systematic review and meta-analysis was planned to generate summarized evidence on the association between maternal serum lipid profiles and pre-eclampsia in African women. Methods Four electronic databases such as; PubMed, Hinari, Google Scholar, and African Journals Online were searched for studies published in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
(88 reference statements)
7
9
0
2
Order By: Relevance
“…Our findings are in agreement with the studies of Makedou et al, [18] and Tesfa et al, [19] who reported that pregnant women presented higher oxidized low-density lipoprotein levels than non-pregnant control hence, predisposing them to preeclampsia and other pregnancy complications. Also, the level of oxidized low-density lipoprotein in the first and third trimester (3716±599.86pg/ml and 4031.98±103.50 respectively) was higher in the pregnant women than in the control.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are in agreement with the studies of Makedou et al, [18] and Tesfa et al, [19] who reported that pregnant women presented higher oxidized low-density lipoprotein levels than non-pregnant control hence, predisposing them to preeclampsia and other pregnancy complications. Also, the level of oxidized low-density lipoprotein in the first and third trimester (3716±599.86pg/ml and 4031.98±103.50 respectively) was higher in the pregnant women than in the control.…”
Section: Discussionsupporting
confidence: 94%
“…Similar lipid profile variations in preeclampsia have been reported in other studies [13,14,24,25,26]. A meta-analysis of studies examining lipids in pregnancy documented "increased levels of total cholesterol, triglycerides, low-density lipoprotein and other non-high-density lipoproteins with a significantly reduced level of high-density lipoprotein in the third trimesters in preeclampsia" [27]. These observations were different from that of Olalare et al, [18] who reported no difference.…”
Section: Discussionsupporting
confidence: 66%
“…Serum fatty acid consists of different fatty acid fractions, including long-chain polyunsaturated fatty acid (LCPUFA), monounsaturated fatty acid (MUFA) and saturated fatty acid (SFA), together with all of their fractions. A lipidomic analysis showed a different role of this fatty acid in the pathogenesis of the disease [ 9 12 ]. Omega-3 LCPUFA and omega-6 fraction are precursors of prostanoids and leukotrienes involved in inflammation, vasoconstriction, oxidative stress, and platelet aggregation [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%